Short-term forecasting of daily COVID-19 cases in Brazil by using the Holt’s model (SciELO Preprints, 2020)
Introduction: We evaluated the performance of the Holt’s model to forecast the daily COVID-19 reported cases in Brazil and three Brazilian states. Methods: We chose the date of the first COVID-19 case to April 25, 2020, as the training period, and April 26 to May 3, 2020, as the test period. Results: The Holt’s model performed well in forecasting the cases in Brazil and in São Paulo and Minas Gerais states, but the forecasts were underestimated in Rio de Janeiro state. Conclusions: The Holt’s model can be an adequate shortterm forecasting method if their assumptions are adequately verified and validated by experts.